Case Report: Prenatal Diagnosis of Postaxial Polydactyly With Bi-Allelic Variants in Smoothened (SMO) - Fan, Lihong; Jin, Pengzhen; Qian, Yeqing; Shen, Guosong; Shen, Xueping; Dong, Minyue (Frontiers in Genetics, 2022)
Postaxial polydactyly is a common congenital malformation, which involves complex genetic factors. This retrospective study analyzed the cytogenetic and molecular results of a Chinese fetus diagnosed with postaxial polydactyly of all four limbs. Fetal karyotyping and chromosomal microarray analysis (CMA) did not find any abnormality while trio whole exome sequencing (Trio-WES) identified bi-allelic variants in smoothened (SMO): (NM_005631.5: c.1219C>G, NP_005622.1: p. Pro407Ala; NM_005631.5: c.1619C>T, NP_005622.1: p. Ala540Val). Sanger sequencing validated these variants. The mutations are highly conserved across multiple species. In-depth bioinformatics analysis and familial cosegregation implied the compound heterozygous variants as the likely cause of postaxial polydactyly on this fetus. Our findings provided the basis for genetic counseling and will contribute to a better understanding of the complex genetic mechanism that underlies postaxial polydactyly.